Economic Analysis of Potato Seed in West Java, Indonesia - Ginandjar, Salamet; Rahmadi, Agung; Abdulhakim, Muhammad Tsani; Subandi, M (Asian Journal of Agriculture and Rural Development, 2020)
The purpose of this study was to study the supply of potato seed in West Java, Indonesia. The research respondent is farmers who use seed, with a sample of 377 farmers and a survey of all seed breeders totaling 43 farmers, using proportionate stratified random sampling. This research report is also complemented by a review analysis of potato seedling development in the last five years. There is considerable interest in the potential that can be developed, productive aged farmers, and adoption of new technologies. Factors exerting a strong influence include capital, technology, adequacy of seed, the proportion of certified seed, and farm credit. Factors identified as influencing the level of demand include the proportion of certified seed, seed prices, capital, and credit allocation for potato farming; at the level of supply factors that can exert influence are the availability of seed, the selling price of seed, and the capital of breeding farmers. Policy simulation on the use of certified seed potatoes shows that increase in the number of specific farm credits, the price of seed and fixed farm capital results in increased use of certified seed and reduced self-selection of seed.